Pola Pembentukan Karakter Santri Preneur Di Pondok Pesantren Kuno Mlangi Yogyakarta - Nur Kholik (PT. Nawa Edukasi Nusantara, 2025)
Entering the competitive era, the tradition of Islamic boarding schools that teach religious knowledge and positive character as living values in society has played a major role in improving the welfare of the people, including the economic sector. This research aims to find out the management of entrepreneurship education at the Mlangi Ancient Islamic Boarding School, Yogyakarta. As a qualitative research, the data collection methods used are; interviews, direct observations, and documentation and phenomenological approaches. The results of the study show; 1) Entrepreneurship education planning at the Mlangi Ancient Islamic Boarding School in Yogyakarta is carried out in three forms, namely theory-based planning, practice-based planning and planning in the form of hidden curriculum. 2) In its implementation, entrepreneurship education at the Mlangi Ancient Islamic Boarding School in Yogyakarta not only emphasizes the understanding of theory, but also the practical aspect. 3) Evaluation using the CIPP (Context, Input, Process, and Product) model.